Work-life enrichment - Zaiton, Hassan; Paula, Brough; Michael, O’Driscoll (Springer Netherlands, 2014)
Work-life enrichment describes how positive experiences in work and non-work (home) lives interact to produce gains in satisfaction, health and performance. In this chapter we discuss the antecedents of work-life enrichment, including social support, a supportive workplace culture and family-friendly human resource policies. The chapter also discusses the consequences of work-life enrichment, including increased job satisfaction, commitment, work engagement, work performance, individual health and family satisfaction. We briefly review the key moderators and mediators of work-life enrichment and provide two examples of effective work-life enrichment research from within the Asia-Pacific region. Finally, we discuss future research directions of work-life enrichment, including the necessity to better assess the impact of both organisational policies and individual coping mechanisms upon levels of work-life enrichment.